Electric Insulation Detection Method for High-voltage Insulators - Wang Jiajun; Hong Bin; Wang Hongmei (Institute of Advanced Engineering and Science, 2013)
The principle of partial discharge detection is that through partial bridged discharge under high voltage electric field, it detects the inner air-filled cavity of high-voltage insulators. And it is a nondestructive detection method based on discharge magnitude to judge the insulation quality. The detecting system that adopts the partial discharge detection is more rigorous than testing system for electricity products, which must have small discharge capacity and higher sensitivity. This paper describes the principles of partial discharge detection and analysis insulation detection. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2862